Production control and supplier selection under demand disruptions - Xianzhe Chen; Jun Zhang (Journal of Industrial Engineering and Management (JIEM), 2010)
This paper investigates the effects of demand disruptions on production control and supplier selection in a three-echelon supply chain system. The customer demand is modeled as a jump-diffusion process in a continuous-time setting. A two-number production-inventory policy is implemented in the production control model for the manufacturer. The objective is to minimize the long-term average total cost consisting of backlog cost, holding cost, switching cost, and ordering cost. The simulated annealing method is applied to search the optimal critical switching values. Furthermore, an improved analytical hierarchy process (AHP) is proposed to select the best supplier, based on quantitative factors such as the optimal long-term total cost obtained through the simulated annealing method under demand disruptions and qualitative factors such as quality and service. Numerical studies are conducted to demonstrate the effects of demand disruptions in the face of various risk scenarios. Managerial insights from simulation results are provided as well. Our approaches can be implemented as the "stress test" for companies in front of various supply chain disruption scenarios.
Keywords: 650; supplier selection; demand disruption; simulated annealing; jump diffusion process; analytical hierarchy process